A case study of how a sample of preservice teachers made sense of incorporating iPads into their instruction with children. Issue 1 (2nd January 2017) - Brown, Christopher P.; Englehardt, Joanna
ABSTRACT: The increased use of and demand for technology in early childhood education classrooms and programs creates new challenges for practicing and preservice early educators being asked to employ such technology within their teaching. Early childhood teacher education programs have struggled to meet these demands for teaching their students how to integrate such technology into their instruction with young children. Preservice teachers who do receive such training often fail to develop the skills and/or beliefs required to implement technology effectively into their own classrooms. The study reported on in this article addresses this issue by providing insight into how a sample of early childhood preservice teachers who used iPads and their apps in their coursework and high-stakes early learning field placements made sense of using these devices as teachers. Such findings illuminate instructional opportunities for teacher educators to consider as they seek to assist their students in making sense about how to implement as well as adopt appropriate and effective instructional strategies into their own classrooms.